Нагрузочная способность модифицированных глобоидных передач - Гудов, Е. А.; Лагутин, С. А.; Федотов, Б. Ф. (НТУ "ХПИ", 2011)
Рассмотрены методы геометрического и технологического расчета глобоидных передач, модифицированных методом "аи"; при нарезании зубьев колеса двух- и четырехрезцовыми летучками. Показано, что такие передачи отличаются от передач с цилиндрическими червяками более высокой нагрузочной способностью, особенно при больших межосевых расстояниях. Детально описан алгоритм оценки нагрузочной способности. Все предложенные методы и алгоритмы проверены практикой проектирования и производства передач, применяемых в нажимных механизмах прокатных станов, нефтяных насосах, мешалках и другом оборудовании ВАТ "ЭЗТМ" и ряда машиностроительных заводов.

The technique of geometrical and technological design is considered for the globoid gears modified by an increase of machine center distance and gear ratio at the worm cutting in relation to the same parameters of worm drive. It is shown that they differ from one-enveloping worm gears with higher loading capacity, especially at the big center distances. The algorithm for the assessment of loading capacity of gears is described in details. All offered methods and algorithms are verified by practice of design and manufacture of modified globoid gears for adjustment devices of rolling mills, oil pumps, mixers and other equipment at the Joint Stock Co "EZTM" (Electrostal Plant of Heavy Machines) and a number of other plants.
Keywords: передача червячная; зацепление; радиус кривизны; грузоподъёмность